2021
DOI: 10.3390/ijms22073666
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic NCR Peptide Fragments Affect the Viability, Morphology and Biofilm Formation of Candida Species

Abstract: The increasing rate of fungal infections causes global problems not only in human healthcare but agriculture as well. To combat fungal pathogens limited numbers of antifungal agents are available therefore alternative drugs are needed. Antimicrobial peptides are potent candidates because of their broad activity spectrum and their diverse mode of actions. The model legume Medicago truncatula produces >700 nodule specific cysteine-rich (NCR) peptides in symbiosis and many of them have in vitro antimicrobial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Other peptide derivatives, cysteine-rich (NCR) peptides NCR335 and NCR169 derivatives, could reduce both biofilm formation and hyphal development of Candida strains examined [ 84 ]. As recently reviewed, the antimicrobial peptides could have a wide application in both human and veterinary medicine including as antifungals [ 124 ].…”
Section: Recent Update On Antifungal Targets and Strategiesmentioning
confidence: 99%
“…Other peptide derivatives, cysteine-rich (NCR) peptides NCR335 and NCR169 derivatives, could reduce both biofilm formation and hyphal development of Candida strains examined [ 84 ]. As recently reviewed, the antimicrobial peptides could have a wide application in both human and veterinary medicine including as antifungals [ 124 ].…”
Section: Recent Update On Antifungal Targets and Strategiesmentioning
confidence: 99%
“…Mature MtNCR peptides range in size from 24 to 65 amino acids, but most of them composed of 30–50 amino acids and contain 4 or 6 cysteine residues at conserved positions in a highly variable amino acid sequence ( Mergaert et al, 2003 ; Mergaert, 2018 ; Lima et al, 2020 ; Roy et al, 2020 ). Until now, only a few NCRs have been tested for antimicrobial activity against human, animal and plant pathogenic bacterial and fungal strains ( Tiricz et al, 2013 ; Balogh et al, 2014 ; Ördögh et al, 2014 ; Mikuláss et al, 2016 ; Farkas et al, 2017 ; Montiel et al, 2017 ; Velivelli et al, 2020 ; Isozumi et al, 2021 ; Szerencsés et al, 2021 ). In this respect, the most studied NCR is the highly cationic NCR247 (pI: 10.15) and its derivatives, which are highly effective against ESKAPE pathogens, in most cases outperforming levofloxacin, a third-generation fluoroquinolone antibiotic under laboratory conditions ( Jenei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the most studied NCR is the highly cationic NCR247 (pI: 10.15) and its derivatives, which are highly effective against ESKAPE pathogens, in most cases outperforming levofloxacin, a third-generation fluoroquinolone antibiotic under laboratory conditions ( Jenei et al, 2020 ). The regions responsible for the antimicrobial activity of NCRs were delineated by synthesizing their shorter and substituted derivatives, which in some cases even had increased activity ( Jenei et al, 2020 ; Isozumi et al, 2021 ; Szerencsés et al, 2021 ). The reduced forms of NCR247 and NCR335 were found to be more effective in vitro against the natural symbiont Sinorhizobium meliloti Rm2011 than the oxidized variants forming the disulfide bridges ( Ribeiro et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of the molecular structures of AMPs, investigation of structure-activity relationships, design, chemical synthesis, and testing of smaller fragments or modified analogs of naturally occurring peptides, and the application of chimeras and artificial building blocks are among those strategies that are used to gain valuable pieces of information about AMPs and to improve access to more feasible antimicrobial agents. Our previous studies with defensin-like NCR peptides [ 13 , 14 ] and γ-core peptide derivatives of antifungal proteins [ 15 , 16 , 17 , 18 ] already provide examples of the rational modifications of AMPs in these aspects.…”
mentioning
confidence: 99%
“…Some NCR peptides demonstrate not only antibacterial but also antifungal effects. We showed that both the N- and C-terminal regions of NCR335, as well as the C-terminal sequence of NCR169, possessed anti- Candida activity [ 14 ].…”
mentioning
confidence: 99%